Long‐term hospitalisation rates among 5‐year survivors of Hodgkin lymphoma in adolescence or young adulthood: A nationwide cohort study. Issue 10 (14th March 2017) - Rugbjerg, Kathrine; Maraldo, Maja; Aznar, Marianne C.; Cutter, David J.; Darby, Sarah C.; Specht, Lena; Olsen, Jørgen H.
Abstract : In the present study, we report on the full range of physical diseases acquired by survivors of Hodgkin lymphoma diagnosed in adolescence or young adulthood. In a Danish nationwide population‐based cohort study, 1, 768 five‐year survivors of Hodgkin lymphoma diagnosed at ages 15–39 years during 1943–2004 and 228, 447 comparison subjects matched to survivors on age and year of birth were included. Hospital discharge diagnoses and bed‐days during 1977–2010 were obtained from the Danish Patient Register for 145 specific disease categories gathered in 14 main diagnostic groups. The analysis was conducted separately on three subcohorts of survivors, that is, survivors diagnosed 1943–1976 for whom we had no information on rehospitalisation for Hodgkin lymphoma and survivors diagnosed 1977–2004, split into a subcohort with no expected relapses and a subcohort for whom a rehospitalisation for Hodgkin lymphoma indicated a relapse. The overall standardised hospitalisation rate ratios (RRs) were 2.0 [95% confidence interval (CI), 1.9–2.1], 1.5 (1.4–1.6) and 2.9 (2.6–3.1) respectively, and the corresponding RRs for bed‐days were 3.5 (3.4–3.5), 1.8 (1.8–1.9) and 10.4 (10.3–10.6). Highest RRs were seen for nonmalignant haematological conditions (RR: 2.6; 3.1 and 9.7), malignant neoplasms (RR: 3.2; 2.5 and 4.7) and all infections combined (RR: 2.5; 2.2 and 5.3). Survivors of Hodgkin lymphoma in adolescence or young adulthood are at increased risk for a wide range of diseases that require hospitalisation. The risk depends on calendar period of treatment and on whether the survivors were rehospitalised for Hodgkin lymphoma, and thus likely had a relapse. Abstract : What's new? Excellent survival rates for Hodgkin lymphoma have allowed increasing numbers of patients to enjoy a normal, disease‐free life expectancy. Nonetheless, for some, premature death remains a concern, owing to the risk of late effects, including second malignant neoplasms, from curative therapy. The authors of the present study quantified the burden of new diagnoses in Hodgkin lymphoma survivors, showing that among 1, 768 five‐year survivors diagnosed in adolescence or young adulthood from 1943 to 2004, a significant proportion later suffered conditions requiring hospitalisation. Malignant neoplasms, infections and circulatory diseases accounted for the majority of new diagnoses.